Occupational electromagnetic spectrum hazards and the significance of artificial optical radiation: country report for Greece: Risk assessment of the electromagnetic spectrum - Gourzoulidis, George A; Karabetsos, Efthymios; Bourousis, Constantinos; Tyrakis, Charilaos; Flouris, Andreas D; Maris, Thomas G; Topalis, Frangiskos V (La Medicina del Lavoro, 2022)
Background: The electromagnetic spectrum spans over an enormous range from 0 up to more than 1020 Hz in the deep ionizing region, significant exposures exist in specific occupational environments. Between the ionizing and the electromagnetic fields (EMF) part of the spectrum, the ‘optical radiation’ (OR) region has specific properties. Comparative and concise evaluation enables action prioritization. Methods: Following the transposition and implementation periods of the artificial optical radiation (AOR) and EMF European Directives, the Hellenic Ministry of Labour in collaboration with the Greek Atomic Energy Commission (EEAE) and the National Technical University of Athens, conducted thorough occupational exposure investigation in Greece. Using dedicated measuring equipment and procedures, the majority of EMF emitting installations in Greece and also AOR emitting installations including arc welding, lasers and PC monitors has been assessed. Results: Measurement results from occupational settings reveal that it is the non-coherent metal arc welding AOR that can pose even sub-second overexposures. Rare EMF overexposures are manageable and EMF concern is not justified. Maintenance procedures demand proper attention. Preliminary laser safety assessment reveals OHS gaps and potential eye and skin hazards. Blue light exposure from computer monitors is well below safety limits. Conclusions: This electromagnetic spectrum risk assessment conducted in Greece enables the justification of the real occupational hazards, in this sense: i) EMF exposure assessment has to be concentrated to maintenance procedures; ii) AOR measuring setups are challenging and standardized measurement procedures are missing, and iii) AOR overexposures from arc welding pose significant eye and skin hazards.